IMPLEMENTASI PELAYANAN JAMINAN SOSIAL KESEHATAN (JKN) MENURUT UNDANG-UNDANG NOMOR 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) PADA PUSKESMAS MAPADDEGAT KABUPATEN KEPULAUAN MENTAWAI - Warti Setia; Arnal Yanuardi; Nasrizal Nasrizal (Jurnal Public Administration, Business and Rural Develoment Planning, 2023)
Based on the explanations in previous chapters, the authors draw the following conclusions: 1) Implementation of Health Social Security (JKN) services according to Law (UU) Number 24 of 2011 concerning the Social Security Administering Body (BPJS) at the Mapaddegat Health Center, Mentawai Islands Regency namely a) humanity that: there is still a lack of services at the Mapaddegat Health Center in Mentawai Islands Regency, this is because patients have to queue long for treatment, the medicines available at the Public Health Center are only in the form of generic drugs and the lack of chairs in the waiting room for patients at the Mapaddegat Public Health Center, Mentawai Islands Regency. , b) The principle of benefit is that not all people can benefit from Health Social Security Services (JKN) at the Mapaddegat Health Center, Mentawai Islands Regency because of distance, travel time, transportation costs, ability to pay for health services and lack of socialization from the Health Social Security Administration Agency (BPJS). as well as Puske SMAS, c) social justice for all Indonesian people. that at the Mapaddegat Health Center, Mentawai Islands Regency, there is an injustice in giving drugs to patients because of the use of different BPJS classes. 2) Factors that influence the implementation of Health Social Security (JKN) services according to Law (UU) No. 24 of 2011 concerning the Social Security Administering Body (BPJS) for Health at Mapaddegat Health Center, Mentawai Islands Regency, including: human resource factors and the availability of facilities. and infrastructure.